(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Freedom of Conscience and Military Service as seen by the Adventist leader Ștefan Demetrescu in the Wake of the First World War. The suffusion of the Advent belief on the territory of Romania and among Romanians was a novelty for the Romanian society. And new things meet the resistance of the conservatives who do not hesitate to fight against them through various methods. Adventists were often accused of treason, state sabotage and so on. There were isolated cases of Adventist conscience objectors who refused to take the military oath or to carry weapon. Were the accusations justified? What was the position of the Adventist leaders towards military service?